CrN/AlN nanolaminate coatings deposited via high power pulsed and middle frequency pulsed magnetron sputtering - Bagcivan, N.; Bobzin, K.; Ludwig, A.; Grochla, D.; Brugnara, R.H. (Thin solid films, 2014)
Nanolaminate coatings based on transition metal nitrides such as CrN, AlN and TiN deposited via physical vapor deposition (PVD) have shown great advantage as protective coatings on tools and components subject to high loads in tribological applications. By varying the individual layer materials and their thicknesses it is possible to optimize the coating properties, e.g. hardness, Young's modulus and thermal stability. One way for further improvement of coating properties is the use of advanced PVD technologies. High power pulsed magnetron sputtering (HPPMS) is an advancement of pulsed magnetron sputtering (MS). The use of HPPMS allows a better control of the energetic bombardment of the substrate due to the higher ionization degree of metallic species. It provides an opportunity to influence chemical and mechanical properties by varying the process parameters. The present work deals with the development of CrN/AlN nanolaminate coatings in an industrial scale unit by using two different PVD technologies. Therefore, HPPMS and mfMS (middle frequency magnetron sputtering) technologies were used. The bilayer period Λ, i.e. the thickness of a CrN/AlN double layer, was varied between 6.2nm and 47.8nm by varying the rotational speed of the substrate holders. In a second step the highest rotational speed was chosen and further HPPMS CrN/AlN coatings were deposited applying different HPPMS pulse lengths (40, 80, 200μs) at the same mean cathode power and frequency. Thickness, morphology, roughness and phase composition of the coatings were analyzed by means of scanning electron microscopy (SEM), confocal laser microscopy, and X-ray diffraction (XRD), respectively. The chemical composition was determined using glow discharge optical emission spectroscopy (GDOES). Detailed characterization of the nanolaminate was conducted by transmission electron microscopy (TEM). The hardness and the Young's modulus were analyzed by nanoindentation measurements. The residual stress was determined via Si microcantilever curvature measurements. The phase analysis revealed the formation of h-Cr2N, c-CrN and c-AlN mixed phases for the mfMS CrN/AlN coatings, whereas the HPPMS coatings exhibited only cubic phases (c-CrN, c-AlN). A hardness of 31.0GPa was measured for the HPPMS coating with a bilayer period of 6.2nm. The decrease of the HPPMS pulse length at constant mean power leads to a considerable increase of the cathode current on the Cr and Al target associated with an increased ion flux towards the substrate. Furthermore, it was observed that the deposition rate of HPPMS CrN/AlN decreases with shorter pulse lengths, so that a CrN/AlN coating with a bilayer period of 2.9nm, a high hardness of 40.8GPa and a high compressive stress (−4.37GPa) was achieved using a short pulse length of 40μs. •HPPMS and mfMS CrN/AlN nanolaminate coatings were investigated.•HPPMS CrN/AlN coatings were deposited at various pulse lengths.•Decreasing of the HPPMS pulse length leads to a reduction of bilayer period.•HPPMS CrN/AlN coating deposited at short pulse showed a super hardness of 40.8GPa.•Short HPPMS pulse and high peak current lead to high coating compressive stress.